A Study Of User Interface Design Of Mhealth App In China: Femtech Pelvic Floor Muscle Training - Yi, Zao (2024)
With the rise of mobile devices and internet usage, mHealth has gained global prominence in various domains of human health. This study focuses on the mobile application (App) interface design for pelvic floor muscle training (PFMT), which combines mHealth and Femtech.